If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 4x + 5 Reorder the terms: -2 + 3x = 4x + 5 Reorder the terms: -2 + 3x = 5 + 4x Solving -2 + 3x = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 3x + -4x = 5 + 4x + -4x Combine like terms: 3x + -4x = -1x -2 + -1x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + -1x = 5 + 0 -2 + -1x = 5 Add '2' to each side of the equation. -2 + 2 + -1x = 5 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 5 + 2 -1x = 5 + 2 Combine like terms: 5 + 2 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| -42y=66 | | 42y=66 | | -8x-5y=-11 | | 81-x=27 | | 9a=a+60 | | 2b-b^2-15=0 | | 2(2x-8)-5=2(x-3)-1 | | 78507+11.25x=20885+23x | | 6N+6J=N | | 2a-11=3(a+1)+16a+5 | | 3x^2-13w-6w^2=0 | | v=2v-73 | | 7n+6=13+7n | | 16=-2(x+4) | | 5-13w-6w^2=0 | | 4u+18=2u+66 | | 0.20=ln(y) | | .25(x+4)=32 | | 9x^2-36=y | | 8u^2+1u-9=0 | | 28-8k=4(-1-k) | | 6x+-9=2x+7 | | 17x-7=13x+1 | | 6x+-9=2x+-7 | | 3.2=y+5.4 | | 9x-(6x+9)=7x-29 | | 5m-4=3(m+6) | | 4a-7=7(a+1)+14a+6 | | t+30=1 | | 5-2(2m+3)=15 | | 2(10x+3)=5(4x-7) | | -23=5k+7k |